Anti-SARS-CoV-2 Activity of Polysaccharides Extracted from Halymenia floresii and Solieria chordalis (Rhodophyta) - Clément Jousselin; Hugo Pliego-Cortés; Alexia Damour; Magali Garcia; Charles Bodet; Daniel Robledo; Nathalie Bourgougnon; Nicolas Lévêque (Marine Drugs, 2023)
Even after hundreds of clinical trials, the search for new antivirals to treat COVID-19 is still relevant. Carrageenans are seaweed sulfated polysaccharides displaying antiviral activity against a wide range of respiratory viruses. The objective of this work was to study the antiviral properties of Halymenia floresii and Solieria chordalis carrageenans against SARS-CoV-2. Six polysaccharide fractions obtained from H. floresii and S. chordalis by Enzyme-Assisted Extraction (EAE) or Hot Water Extraction (HWE) were tested. The effect of carrageenan on viral replication was assessed during infection of human airway epithelial cells with a clinical strain of SARS-CoV-2. The addition of carrageenans at different times of the infection helped to determine their mechanism of antiviral action. The four polysaccharide fractions isolated from H. floresii displayed antiviral properties while the S. chordalis fractions did not. EAE-purified fractions caused a stronger reduction in viral RNA concentration. Their antiviral action is likely related to an inhibition of the virus attachment to the cell surface. This study confirms that carrageenans could be used as first-line treatment in the respiratory mucosa to inhibit the infection and transmission of SARS-CoV-2. Low production costs, low cytotoxicity, and a broad spectrum of antiviral properties constitute the main strengths of these natural molecules.